Metallization of Silver Through Coffee‐Ring Assisted Ribonucleic Acid Scaffolding Technique - Shakir, Sehar; Talebi, Sara; Abd‐ur‐Rehman, Hafiz Muhammad; Phang, Siew Moi; Iwamoto, Mitsumasa; Yunus, Kamran; Periasamy, Vengadesh (Wiley, 2019)
Preferential binding of base pair units with metallic ions within deoxyribonucleic acids (DNA) to form metal-DNA complexes are well studied and understood. Excitingly, such natural processes have been utilized “artificially” for designing and fabricating nanometallic structures and patterns primarily using double stranded DNA. However, little or no effort has been given to ribonucleic acid or RNA in this aspect. Therefore, in this work we study the scaffolding effect of RNA on metalizing silver (Ag) ions and further the diffusion of majority of the Ag-RNA complexes towards artificially introduced cut or scribed edges as a result of the coffee-ring effect. Upon removal of the RNA scaffold, metallic nanostructures remain along the line of the cut corresponding to the micrometre scale length of the cut, exercising some amount of control and manipulation of parameter. Other parameters such as the height and diameter may directly be related to the concentration and diffusion of the Ag-RNA complexes, while gap size related to the cut width. We anticipate that further in-depth studies will be required before a comprehensive model could be proposed for highly controllable and flexible nanostructure and nanowire fabrication using nucleic acid scaffolding techniques. © 2019 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim